Somatosensory aura in mesial temporal lobe epilepsy: semiologic characteristics, MRI findings and differential diagnosis with parietal lobe epilepsy - Rahal,Márcio Andriani (2006)
INTRODUCTION: Somatosensory auras (SSAs) are more usually described in patients with parietal lobe epilepsy (PLE), producing more commonly a localized cutaneous tingling sensation, involving hands and fingers followed by tonic or clonic focal seizures. These usually originate in the contralateral hemisphere. Etiology includes dysplasias, tumours, ischemic or postencephalitic gliosis. However, other focal epilepsies, such as frontal and temporal, may also originate SSAs. Although this type of aura is reported as rare in patients with mesial temporal lobe epilepsy (MTLE), this association has not been systematically studied. OBJECTIVES: The aim of this article was to describe the cases of four patients with refractory MTLE and SSAs, reporting their clinical characteristics and MRI findings. We discuss the localizing and lateralizing value of SSAs, particularly in the context of MTLE. METHODS AND RESULTS: Four patients with refractory MTLE and SSAs followed-up in the outpatient's clinic at the Epilepsy Section, Universidade Federal de São Paulo, were submitted to presurgical evaluation and corticoamygdalohippocampectomy. MRI in all cases showed unilateral mesial temporal sclerosis (MTS). Regarding seizure semiology, tingling sensation involving the upper extremity was the most prevalent symptom. Three of the four patients had SSAs contralateral to the MTS. Following the SSAs all patients most of the time presented other symptoms such as autonomic or psychic auras evolving to psychomotor seizures. After surgical treatment, two of the patients presented infrequent auras, and two were rendered seizure-free. CONCLUSION: Although rare, SSAs can be present in MTLE. The characteristics of autonomic or psychic auras, psychomotor seizures, neuropsychological deficits, and typical neurophysiologic and MRI findings may help differentiate patients with MTLE from those with PLE.